Effectiveness Comparison of Using Macintosh Blade and Mccoy Blade For Endotracheal Intubation In Anesthesia Residents - Christya Lorena; Agustina Salinding; Prananda Surya Airlangga (Faculty of Medicine-Universitas Airlangga, 2021)
Introduction: Laryngoscopy is one of the critical points in the intubation process and a mechanical trauma that provides noxious stimulation, affecting cardiovascular, respiratory, and intracranial changes. Practitioner competence is a significant factor that supports laryngoscope intubation procedures. That can influence the intubation duration and amount of mechanical trauma besides caused by laryngoscope type. Objective: To analyze the effectiveness of using Macintosh blade compared to McCoy blade in intubation laryngoscopy by Anesthesia Residents. Materials and Methods: This research is an experimental study in adult patients who underwent elective surgery at GBPT Dr. Soetomo Hospital. Intubation did by Anesthesia Residents at levels 5-9 using Macintosh or McCoy Laryngoscope and chosen randomly. The data of laryngeal visualization (Cormack Lehane), hemodynamics (blood pressure, pulse), pain scale (qNOX), intubation time length, and pain scale data (VAS) after extubation were taken during intubation laryngoscope. Result and Discussion: The study was conducted on 28 samples that met the criteria. Anesthesia Resident's competence levels based on the semester in both groups laryngoscopes were not different (p 0.868). Based on laryngeal visualization data laryngoscopy, the McCoy's blade had better visualization with CL 1 at 85.7% of the samples and p-value 0.020. This good visualization makes it possible to speed up the laryngoscope-intubation in the McCoy blade group with a significant difference of time compared to the Macintosh blade group. Hemodynamic parameters, there were significant differences for hemodynamics increase. In the Macintosh blade group, the blood pressure and pulse were significantly increased after laryngoscopy intubation. The pain scale during the intubation procedure, which was rated based on the qNOx score, showed a significant increase in the Macintosh blade group with a p-value of 0.003. The postoperative pain scale (VAS) was smaller in the McCoy blade group compared to the Macintosh group (p-value <0.001). Conclusion: The ability to use both laryngoscopes at some levels of Anesthesia residents was equally good, and the use of McCoy Blade is more effective than Macintosh Blade in the intubation laryngoscopy procedure.